1997
DOI: 10.1123/ijsn.7.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Allithiamine Ingestion Does Not Enhance Isokinetic Parameters of Muscle Performance

Abstract: The purpose of this study was to investigate the effect of oral allithiamine administration on isokinetic parameters of muscle performance and lactate accumulation prior to, during, and in recovery from isokinetic exercise. A double-blind, counterbalanced, crossover experimental design utilizing aBiodex System 2 Isokinetic Dynamometer was used to test 15 healthy college students. Subjects orally ingested either 1 g · of a thiamin derivative, allithiamine, or a placebo for 5 days and then performed six exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…(1972) reported improvements in leg and grip strength after ingestion of 150 mg of allithiamin á day A1 . In contrast, Doyle et al (1997) demonstrated no changes in isokinetic muscle performance or blood La A accumulation with the ingestion of 1 g of allithiamin á day A1 for 5 days. This is in agreement with a recent study demonstrating no changes in submaximal O 2 , O 2max , blood La A accumulation, La A threshold, or cycling performance time after the ingestion of 1 g of allithiamin á days A1 for 3±4 days .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…(1972) reported improvements in leg and grip strength after ingestion of 150 mg of allithiamin á day A1 . In contrast, Doyle et al (1997) demonstrated no changes in isokinetic muscle performance or blood La A accumulation with the ingestion of 1 g of allithiamin á day A1 for 5 days. This is in agreement with a recent study demonstrating no changes in submaximal O 2 , O 2max , blood La A accumulation, La A threshold, or cycling performance time after the ingestion of 1 g of allithiamin á days A1 for 3±4 days .…”
Section: Discussionmentioning
confidence: 82%
“…The relatively few studies investigating allithiamin ingestion and exercise performance report con¯icting results (Nishiyama et al 1972;Doyle et al 1997;Webster et al 1997). Nishiyama et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, Doyle et al . [21] and Webster [22] propose that the TTFD intake does not affect exercise performance. Studies observing the effect of single administration of thiamine do not reach a clear conclusion and the one week supplementation period is too short requiring investigation on the effect on long-term supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been just recently that these compounds received approval for use in the United States of America. Only two studies investigating the eect of allithiamins on exercise performance have been reported in the literature (Doyle et al 1997;Nishiyama et al 1972). Doyle et al (1997) reported no changes in lactate accumulation or isokinetic work and power output by the quadriceps and hamstring muscle groups after a 5-day supplementation with 1 g á day )1 of TTFD.…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies investigating the eect of allithiamins on exercise performance have been reported in the literature (Doyle et al 1997;Nishiyama et al 1972). Doyle et al (1997) reported no changes in lactate accumulation or isokinetic work and power output by the quadriceps and hamstring muscle groups after a 5-day supplementation with 1 g á day )1 of TTFD. In contrast, Nishiyama et al (1972) reported signi®cant improvements in grip strength and vertical jump with the administration of 150 mg á day )1 .…”
Section: Introductionmentioning
confidence: 99%